Dietary Supplementation of Ferrous Glycine Chelate Improves Growth Performance of Piglets by Enhancing Serum Immune Antioxidant Properties, Modulating Microbial Structure and Its Metabolic Function in the Early Stage - Ma, Jiayu; Liu, Sujie; Piao, Xiangshu; Wang, Chunlin; Wang, Jian; Lin, Yu-sheng; Hsu, Tzu-ping; Liu, Li (Frontiers in Veterinary Science, 2022)
The aim of present research was to explore the effect of dietary ferrous glycine chelate supplementation on performance, serum immune-antioxidant parameters, fecal volatile fatty acids and microbiota in weaned piglets. A total of 80 healthy piglets (weaned at 28d with initial weight 7.43 ± 1.51 kg) were separated into 2 treatments with 5 replicates of 8 pigs each following a completely randomized block design. The dietary was corn-soybean basal diet with 2,000 mg/kg ferrous glycine chelates (FGC) or not (Ctrl). The serum and fecal samples were collected on 14d and 28d of the experiment. The results indicated that dietary FGC supplementation improved (P < 0.05) the average daily gain and average daily feed intake overall, alleviated (P < 0.05) the diarrhea rate of piglets at early stage, enhanced (P < 0.05) the levels of superoxide dismutase and catalase on d 14 and lowered (P < 0.05) the MDA level overall. Similarly, the levels of growth hormone and serum iron were increased (P < 0.05) in FGC group. Moreover, dietary FGC supplementation was capable of modulating the microbial community structure of piglet in the early period, increasing (P < 0.05) the abundance of short-chain fatty acid producing bacteria Tezzerella, decreasing (P < 0.05) the abundance of potentially pathogenic bacteria Slackia, Olsenella and Prevotella as well as stimulating (P < 0.05) the propanoate and butanoate metabolisms. Briefly, dietary supplemented FGC ameliorate the performance and alleviated the diarrhea of piglets by enhancing antioxidant properties, improving iron transport and utilization, up-regulating the growth hormone, modulating the fecal microbiota and increasing the metabolism function. Therefore, FGC is effective for early iron supplementation and growth of piglets and may be more effective in neonatal piglets